Microsatellite Markers Determine the Genetic Structure and Diversity of Landraces of Quinoa from Ayacucho, Peru - Germán De la Cruz; Carla L. Saldaña; Francisco Menéndez; Edgar Neyra; Carlos I. Arbizu (Agronomy)
Quinoa (Chenopodium quinoa, Amaranthaceae) is a pseudocereal native to the Andes of South America that contains high protein content and adequate nutrient levels. Peru possesses an abundant morphological diversity of quinoas and is among the top producers and exporters worldwide of this precious crop. However, knowledge about the genetic and population components of quinoa from the Peruvian Andes is still limited. Here, we used 13 microsatellite markers to determine the genetic diversity and population structure of 105 landraces of quinoa cultivated in 11 provinces of Ayacucho, the southern Peruvian Andes. A total of 285 bands were manually scored, generating a 105 × 285 presence/absence data set. Principal coordinate analysis, similar to a dendrogram using the UPGMA clustering algorithm, showed that quinoa from Ayacucho is grouped into three clusters without a clear geographic component. Estimation of the genetic diversity indices was conducted considering the three populations (C1: south 1, C2: south 2, C3: north) determined by STRUCTURE analysis, showing mean expected heterozygosity was 0.08, which may be attributed to high rates of inbreeding and genetic drift, as Ayacucho suffered decades of sociopolitical violence, promoting the migration of farmers. The highest population divergence (FST) was exhibited for C2 and C3 (0.03), whereas the lowest was for C1 and C3 (0.02). Analysis of molecular variance revealed the greatest variation within populations (80.07%) and indicated that variability between populations is 19.93%. Microsatellite markers were effective; however, more studies of the genetic components of quinoa from other Peruvian Andean localities are still needed. We expect that this work will help pave the way towards the development of modern breeding programs of quinoa in Peru, with accurate strategies for the conservation of this nutritious crop.